Multilayer Film with Controlled Interfacial Peel Strength for Cosmetic Containers
A multilayer film for cosmetic containers with controlled peeling force distribution and adhesive force management addresses issues of inconsistent peeling and structural instability, ensuring stable opening and long-term preservation by uniformly controlling peeling initiation and propagation.
Patent Information
- Application Number
- KR1020260061499
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2026-04-06
- Publication Date
- 2026-11-05
- Estimated Expiration
- 2046-04-06
AI Technical Summary
Conventional films for cosmetic containers face issues with inconsistent peeling forces, leading to unpredictable peeling initiation and propagation, structural instability, and content scattering due to excessive peeling force or rapid delamination, while maintaining high barrier properties against oxygen, moisture, and volatile components.
A multilayer film structure comprising a substrate layer, high barrier layer, interface peeling force control layer, and protective layer, designed through co-extrusion with precise control of adhesive force distribution and peeling behavior using synthetic beads and inorganic particles, ensuring uniform peeling initiation and propagation.
The film provides stable opening sensation, prevents content scattering, maintains structural integrity during storage and transportation, and effectively blocks oxygen and moisture, ensuring long-term preservation of cosmetic contents.
Smart Images

Figure 112026041331699-PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to the field of film coating technology, and more specifically, to an interface peeling force control type easy peeling high barrier film that maintains adhesion stability and high barrier properties of the film layer during the usage stage and enables easy peeling during the recycling stage by precisely controlling the peeling force at the interface between the container body and the film layer, and a cosmetic container including the same. Background Technology
[0002] Films applied to cosmetic containers are required to provide barrier properties against oxygen, moisture, and volatile components to prevent the deterioration of the contents and ensure long-term preservation, while simultaneously requiring easy-peel properties that allow the user to easily peel off the film upon opening. Since liquid or semi-solid cosmetics such as essences, creams, and foundations may undergo oxidation or component degradation upon contact with external air, the high barrier properties of the film serve as an important factor in maintaining product quality.
[0003] Conventional films for cosmetic containers often employ a multi-layer structure to ensure barrier properties, featuring a design where adhesion between layers is uniformly formed. However, such structures can lead to problems, such as excessive peeling force upon opening or rapid delamination at specific interfaces, causing the contents to scatter. Furthermore, when adhesive strength is simply reduced to lower peeling force, issues arise such as interlayer delamination during storage or a decrease in the film's structural stability during transportation and handling.
[0004] In conventional technology, methods involving changing specific resin compositions or the thickness of the adhesive layer are primarily used to control peel strength; however, since these methods result in a structure that forms uniform adhesive characteristics across the entire interface, the peel initiation and propagation processes are not precisely controlled. Consequently, it is difficult to ensure uniformity in the opening sensation perceived by the user, and if localized stress concentration occurs in specific areas of the film, problems such as fracture progressing in unpredictable directions or film tearing may occur. Prior art literature
[0005] Republic of Korea Published Patent 10-2018-0088077 (Published Aug. 3, 2018) The problem to be solved
[0006] The present invention aims to provide a multilayer film for cosmetic containers that allows the user to feel a consistent and stable opening sensation by controlling the peeling initiation position and peeling progression characteristics at the interface while maintaining excellent barrier properties against oxygen, moisture, and volatile components in a film for cosmetic containers.
[0007] In addition, the present invention aims to provide a multilayer film for cosmetic containers that can maintain stability during transportation and storage by controlling the distribution of adhesive force at each interface within a multilayer structure to prevent scattering of contents caused by excessive peeling force or rapid peeling, and by suppressing interlayer delamination or structural instability during storage.
[0008] In addition, the present invention aims to provide a multilayer film for cosmetic containers that can precisely control peeling initiation and propagation behavior and simultaneously secure mechanical strength and interfacial stability of the film by combining a structural layer formed by co-extrusion with an interface control means selectively applied. means of solving the problem
[0009] An interface peeling control type multilayer film for a cosmetic container according to one embodiment of the present invention may include a substrate layer, a high barrier layer laminated on the substrate layer, an interface peeling force control layer laminated on the high barrier layer, and a protective layer laminated on the interface peeling force control layer.
[0010] The above substrate layer may be formed into a multilayer structure including polyethylene terephthalate, polypropylene, and polyamide.
[0011] The above high barrier layer may include an ethylene-vinyl alcohol copolymer, polyvinylidene chloride, and polyamide.
[0012] The above protective layer may include fluorine-based resin, silicone-based resin, and urethane-based resin.
[0013] The above interface peel force control layer may include a first interface adhesion control layer, a second stress buffering layer, a third peel inducing layer, and a fourth protective fusion layer.
[0014] The first interface adhesion control layer, the second stress buffering layer, and the third peel-inducing layer can be integrally formed by a multilayer co-extrusion process.
[0015] The above-mentioned high-barrier layer or protective layer may include synthetic beads.
[0016] The above synthetic beads may be formed from at least one of acrylic, polystyrene, polymethyl methacrylate, urethane, and melamine resin.
[0017] The above-mentioned high-barrier layer or protective layer may contain inorganic particles.
[0018] The above inorganic particles may include at least one of nano clay, graphene oxide, plate-like silica, and plate-like alumina.
[0019] The above-mentioned inorganic particles have a core-shell structure, the core comprises silica or alumina, and the shell can be surface modified with a silane-based or organic polymer. Effects of the invention
[0020] The present invention relates to a film for cosmetic containers and has the advantage of preventing spoilage of the contents and improving long-term preservation by effectively suppressing the permeation of oxygen, moisture, and volatile components through a multilayer structure.
[0021] In addition, the present invention has the advantage of preventing scattering of contents caused by excessive peeling force or sudden peeling and providing a stable opening sensation by controlling the distribution of peeling force by interface so that peeling initiation occurs uniformly upon opening rather than being concentrated at a specific point.
[0022] In addition, the present invention has the advantage of suppressing interlayer delamination or structural instability during storage and maintaining the physical stability of the film during transportation and handling by controlling the delamination initiation and propagation behavior through a combination of a structural layer and an interface control means.
[0023] In addition, the present invention has the advantage of improving the reliability of use of the film by controlling the stress distribution at the interface to prevent abnormal fracture or tearing caused by localized stress concentration in specific areas of the film. Brief explanation of the drawing
[0024] FIG. 1 is a cross-sectional view of an interface peeling control type multilayer film for a cosmetic container according to one embodiment of the present invention. Specific details for implementing the invention
[0025] An interface peeling force-controlled easy peeling high barrier film (100) according to one embodiment of the present invention may have a structure in which the peeling force at the interface is controlled so that it can be attached to a container body to prevent oxidation and deterioration of the cosmetic contents, and at the same time be easily separated from the container body during recycling.
[0026] The above high-barrier film (100) may include a substrate layer (110), a high-barrier layer (120), an interface peeling force control layer (130), and a protective layer (140), and each layer may have a structure in which they are sequentially stacked based on the substrate layer (110).
[0027] <Recording layer (110)>
[0028] The above substrate layer (110) is a layer for securing the mechanical strength of the film and is formed of a synthetic resin material to support the entire film structure. The above substrate layer (110) provides flexibility and durability to the film, allowing it to be stably applied to the surface of containers of various shapes.
[0029] In addition, the above substrate layer (110) can perform the function of controlling the peeling initiation position and peeling propagation behavior by pre-designing the stress transfer path and surface energy distribution occurring at the interface between the above high-blocking layer (120) and the interface peeling force control layer (130).
[0030] The above substrate layer (110) may include a first substrate layer (111), a second substrate layer (112), and a third substrate layer (113), and each layer may be designed to have different material compositions and physical properties. The first substrate layer (111), the second substrate layer (112), and the third substrate layer (113) may have a stacked functional sharing structure so that rigidity-buffering-interface control functions are sequentially expressed.
[0031] The first substrate layer (111) is a layer for securing the mechanical strength and heat resistance of the film (100) and may include one or more materials selected from the group consisting of polyethylene terephthalate (PET), polypropylene (PP), and polyamide (PA). Preferably, the first substrate layer (111) may be formed with a composition comprising 40 to 70 weight% PET, 10 to 30 weight% PP, and 10 to 30 weight% PA. In this case, if the PET content is less than 40 weight%, mechanical strength and dimensional stability may be reduced, and if it exceeds 70 weight%, flexibility may be reduced. Additionally, if PP is less than 10 weight%, processability may be reduced, and if it exceeds 30 weight%, heat resistance may be reduced. PA plays a role in supplementing impact resistance and heat resistance; if it is less than 10 weight%, the effect is negligible, and if it exceeds 30 weight%, a decrease in physical properties due to moisture absorption may occur. In addition, the first substrate layer (111) may further include a maleic anhydride-modified polyolefin or an epoxy-based reactive compatibilizer to improve compatibility and interfacial adhesion between heterogeneous resins.
[0032] Accordingly, the first substrate layer (111) provides a shape-maintaining force against external force, thereby preventing the entire film from being deformed during peeling and inducing the peeling stress to concentrate at the interface.
[0033] The second substrate layer (112) is a layer located between the first substrate layer (111) and the third substrate layer (113) that performs interlayer adhesion and stress relief functions, and may include ethylene-vinyl alcohol copolymer (EVOH), polyurethane (PU), and polyethylene (PE). Preferably, it may be formed with a composition of 30 to 60 wt% EVOH, 20 to 40 wt% PU, and 10 to 30 wt% PE. If the EVOH content is less than 30 wt%, the oxygen barrier performance may be reduced, and if it exceeds 60 wt%, brittleness may increase. PU provides flexibility and interlayer adhesion; if it is less than 20 wt%, the effect of improving adhesion is negligible, and if it exceeds 40 wt%, the strength of the entire film may be reduced. PE complements processability and flexibility; if it is less than 10 wt%, processability is reduced, and if it exceeds 30 wt%, barrier performance may be reduced.
[0034] The above polyurethane (PU) may be a thermoplastic polyurethane (TPU), and the second substrate layer (112) may be formed to have a relatively high elongation and function as a buffer layer that absorbs and disperses interlayer stress.
[0035] The second substrate layer (112) can gradually attenuate the stress transmitted from the first substrate layer (111), thereby suppressing stress concentration at the interface and preventing the peeling initiation force from fluctuating depending on the location.
[0036] The third substrate layer (113) is a layer that is disposed adjacent to the high barrier layer (120) to ensure uniformity of interface characteristics, and may include polycarbonate (PC), acrylic resin (PMMA), and polystyrene (PS). Preferably, it may be formed with a composition comprising 30 to 60 weight% of PC, 20 to 40 weight% of PMMA, and 10 to 30 weight% of PS. If the content of PC is less than 30 weight%, impact resistance may be reduced, and if it exceeds 60 weight%, processability may be reduced. PMMA provides transparency and surface smoothness; if it is less than 20 weight%, the effect is negligible, and if it exceeds 40 weight%, brittleness may increase. PS is advantageous in terms of processability and cost, but if it is less than 10 weight%, the effect is negligible, and if it exceeds 30 weight%, impact resistance may be reduced.
[0037] The above third substrate layer (113) can function as an interface design layer that stabilizes peeling initiation force and peeling propagation behavior by controlling surface energy, elastic modulus, and fine roughness characteristics at the interface with the above high barrier layer (120).
[0038] In addition, the third substrate layer (113) is designed so that the energy release rate at the interface is maintained uniformly within the plane, thereby minimizing deviations in the peeling initiation position and simultaneously enabling the peeling propagation to spread stably without concentrating in a specific path.
[0039] The first substrate layer (111), the second substrate layer (112), and the third substrate layer (113) can be laminated by thermal fusion, co-extrusion, or lamination using an adhesive, and preferably, the interfacial bonding strength can be uniformly formed through a co-extrusion process. Additionally, a primer layer to improve interlayer adhesion strength may be optionally applied, and the primer layer may include an isocyanate-based or epoxy-based adhesive when a lamination process is applied.
[0040] Preferably, the first substrate layer (111), the second substrate layer (112), and the third substrate layer (113) can be laminated through a co-extrusion process, and the co-extrusion process can be performed by simultaneously extruding the molten resin of each layer through a plurality of extruders to form a single multilayer structure. At this time, in order to ensure that the interfacial bonding force between each layer is uniformly formed, the process conditions can be controlled to be interconnected by considering the melting point, thermal stability, and melt viscosity characteristics of each resin.
[0041] Specifically, the first substrate layer (111) may be formed with a composition including PET, PP, and PA, and accordingly, the extrusion temperature may be set in the range of 240 to 270°C. If the temperature is below 240°C, the melting of PET and PA is not sufficiently achieved, which may result in reduced molecular diffusion at the interlayer interface, and if the temperature exceeds 270°C, thermal decomposition or yellowing may occur, which may reduce interfacial stability.
[0042] The second substrate layer (112) may be formed with a composition including EVOH, PU, and PE, and accordingly, the extrusion temperature may be set in the range of 190 to 230°C. If the temperature is below 190°C, the melt viscosity of EVOH may become excessively high, causing uneven interfacial contact with adjacent layers, and if it exceeds 230°C, the thermal stability of EVOH may decrease, causing a decrease in interfacial bonding strength.
[0043] The third substrate layer (113) may be formed with a composition including PC, PMMA, and PS, and accordingly, the extrusion temperature may be set to a range of 220 to 250°C. If the temperature is below 220°C, the melting of PC is insufficient and interfacial adhesion may be reduced, and if it exceeds 250°C, interfacial defects may occur due to the deterioration of PMMA and PS.
[0044] In addition, the melt viscosity of each layer can be controlled to be set in the range of 500 to 3000 Pa·s under the same shear rate conditions, and the viscosity ratio between adjacent layers can be controlled to be maintained in the range of 0.5 to 2.0. If the viscosity ratio is less than 0.5 or exceeds 2.0, an imbalance in interlayer flow may occur, resulting in interfacial waviness or interlayer discontinuity, which may lead to non-uniformity of interfacial peeling force.
[0045] In addition, the extrusion pressure of each layer can be set in the range of 90 to 140 bar, and preferably, the pressure difference between layers can be controlled to be maintained at 5 bar or less. If the extrusion pressure is less than 90 bar, the contact pressure between the molten resins is insufficient, which may lead to the formation of interfacial voids; if it exceeds 140 bar, the interlayer shear stress increases, which may result in internal stress accumulation and interfacial instability. In particular, if the pressure difference exceeds 5 bar, the flow may be concentrated in a specific layer, causing local variations in interfacial thickness and adhesion.
[0046] Meanwhile, the flow rate distribution within the co-extrusion die can be controlled to have a deviation of within ±3% for each layer, and to achieve this, a multi-manifold die or a feed block structure may be applied. If the flow rate deviation exceeds ±3%, the interfacial stress distribution changes due to non-uniformity of layer thickness, which may hinder uniform peel propagation during subsequent peeling.
[0047] Cooling at the die exit can be performed using a cooling roll in the range of 25 to 50°C, and the cooling rate can be controlled in the range of 15 to 40°C / sec. If the cooling rate is less than 15°C / sec, interlayer molecular diffusion may proceed excessively, making the interfacial boundary unclear, and if it exceeds 40°C / sec, solidification may occur before the interfacial bond is sufficiently formed, which may reduce the adhesive strength.
[0048] In addition, the co-extrusion process can be performed in a nitrogen (N₂) atmosphere, and it is desirable to maintain the oxygen concentration at 0.5% or less. If the oxygen concentration exceeds 0.5%, oxidation of the resin proceeds at high temperatures, which may degrade the interfacial adhesion properties.
[0049] In this way, the temperature, viscosity, pressure, flow rate, and cooling conditions are controlled to be interconnected in accordance with the material characteristics of each substrate layer (111, 112, 113), so that molecular diffusion and mechanical bonding at the interlayer interface can be uniformly formed, and the peeling behavior implemented by the subsequent interface peeling force control layer (130) can be expressed consistently and predictably.
[0050] Preferably, the first substrate layer (111), the second substrate layer (112), and the third substrate layer (113) may be formed with thickness ratios of 40-65%, 15-35%, and 10-25%, respectively, relative to the total thickness of the substrate layer (110). The thickness ratios allow the physical properties of each layer to function independently, rather than allowing stress transfer and interfacial energy distribution during the peeling process to be formed in stages.
[0051] If the thickness of the first substrate layer (111) is less than 40%, the mechanical strength and dimensional stability of the entire film may be reduced, and deformation or wrinkling may occur during peeling. If it exceeds 65%, the rigidity of the film may increase excessively, and stress concentration may occur inside the film rather than at the interface during peeling, which may result in uneven fracture or localized peeling.
[0052] If the thickness of the second substrate layer (112) is less than 15%, the interlayer stress relief function is not sufficiently expressed, so stress concentration at the interface increases, and accordingly, the peeling initiation position may become unstable, and if it exceeds 35%, the strength of the entire film decreases, and the structural support strength with the third substrate layer (113) and the high barrier layer (120) decreases, so the handling ability of the film may decrease.
[0053] If the thickness of the third substrate layer (113) is less than 10%, it is difficult to sufficiently control the surface energy and elastic modulus distribution at the contact interface with the high barrier layer (120), so the peeling initiation force may become uneven. If it exceeds 25%, the compliance at the interface decreases, so the peeling propagation does not proceed uniformly along the interface, and partial residue or discontinuous peeling may occur. When the thickness ratio is satisfied, the stress generated in the first substrate layer (111) is buffered through the second substrate layer (112) and converted into an interface energy distribution in the third substrate layer (113), thereby allowing the peeling initiation force, peeling propagation stability, and peeling force deviation to be controlled simultaneously.
[0054] Accordingly, when the thickness ratio described above is satisfied, the rigidity of the first substrate layer (111), the cushioning of the second substrate layer (112), and the interface control function of the third substrate layer (113) are interconnected, and there is an advantage in that the peeling initiation force, peeling propagation stability, and peeling force deviation are controlled within a certain range.
[0056] <Higher-order fault (120)>
[0057] The above-mentioned high-barrier layer (120) can be formed as a functional multilayer structure with interfacial properties designed to effectively block the penetration of oxygen, moisture, and volatile components from the outside to prevent oxidation and deterioration of the cosmetic contents, while simultaneously stably controlling the peeling behavior at the interface with the subsequent interfacial peeling force control layer (130).
[0058] The above-mentioned high-blocking layer (120) has a structure formed on the upper part of the substrate layer (110), and preferably can be formed as a multilayer structure including a first blocking layer (121), a second blocking layer (122), a third blocking layer (123), and a fourth blocking layer (124). At this time, each blocking layer is configured to perform different functions, and in particular, at least some of the blocking layers may include a fine bead structure or an inorganic particle dispersion structure.
[0059] (1) First blocking layer (121)
[0060] The first blocking layer (121) above is a layer that comes into direct contact with the third substrate layer (113), and can secure interfacial adhesion while simultaneously performing an interfacial stress dispersion function.
[0061] The first blocking layer (121) above may have synthetic beads dispersed in a resin including polyethylene (PE), polypropylene (PP), and polyurethane (PU).
[0062] Preferably, the first blocking layer (121) may comprise 40 to 70 weight% PE, 10 to 30 weight% PP, 10 to 30 weight% PU, and 2 to 8 weight% synthetic beads with an average particle size of 1 to 20 μm, based on 100 weight% of the total including synthetic beads.
[0063] Preferably, the synthetic beads may have an average particle size in the range of 3 to 10 μm, and more preferably 5 μm. The synthetic beads may be selected from spherical polymethyl methacrylate (PMMA), polystyrene, urethane, or melamine-based beads, and the interfacial bonding strength with the resin matrix may be improved by treating the surface with a silane coupling agent.
[0064] The synthetic beads may include at least one of acrylic beads, polystyrene beads, polymethyl methacrylate (PMMA) beads, polyurethane beads, polyamide beads, or melamine beads. Preferably, the synthetic beads may include one or more selected from the range of 30-45% by weight of acrylic beads, 10-20% by weight of polystyrene beads, 10-20% by weight of polymethyl methacrylate (PMMA) beads, 5-10% by weight of polyurethane beads, 5-10% by weight of polyamide beads, and 1-5% by weight of melamine beads.
[0065] If the content of the acrylic beads is less than 30% by weight, the surface smoothness and dispersion stability of the beads may be reduced, and if it exceeds 45% by weight, the stiffness of the beads may increase, and interfacial compliance may be reduced. In addition, if the content of polystyrene-based or PMMA beads is less than 10% by weight, shape stability may be insufficient, and if it exceeds 20% by weight, brittleness may increase, and microcracks may occur.
[0066] The average particle size of the above synthetic beads can be set to a range of 1 to 20 μm, preferably 3 to 10 μm.
[0067] If the particle size is less than 1 μm, the formation of a fine spacing structure at the interface is not sufficiently achieved, which may reduce the stress dispersion effect; if it exceeds 20 μm, the increase in roughness of the film surface may lead to interfacial defects and a decrease in blocking performance. Additionally, if the content is less than 2 weight% based on 100 weight% of the total first blocking layer (121), the stress relief effect is negligible, and if it exceeds 8 weight%, the continuous phase of the resin is interrupted, which may reduce the interfacial adhesion.
[0068] The above synthetic beads can be manufactured by suspension polymerization, dispersion polymerization, or emulsion polymerization, and preferably, a suspension polymerization or dispersion polymerization process may be applied so that the particle size distribution and sphericity are uniformly controlled.
[0069] For example, acrylic or PMMA beads can be manufactured using a monomer composition comprising 40 to 80 weight% of methyl methacrylate (MMA), 10 to 40 weight% of butyl acrylate, and 5 to 20 weight% of ethyl acrylate.
[0070] If the MMA content is less than 40% by weight, the shape retention of the beads may be reduced, and if it exceeds 80% by weight, the beads may become excessively hardened, which may reduce interfacial compliance.
[0071] The above synthetic beads can be surface modified using a silane coupling agent, an acrylic treatment agent, or a urethane surface treatment agent, and thereby the interfacial affinity with the resin matrix of the first blocking layer (121) can be improved.
[0072] If the above surface modification is not performed, aggregation of beads may occur, leading to localized interfacial defects, which may result in non-uniformity in blocking performance and peeling behavior.
[0073] The synthetic beads can form a fine spacing structure and a discontinuous stress distribution network at the interface with the third substrate layer (113), thereby alleviating stress concentration across the entire interface and inducing gradual and uniform peeling initiation rather than sudden fracture at a specific point during peeling. In addition, the micro-spatial structure formed by the beads can locally control the interfacial adhesion energy, and in combination with the action of the subsequent interfacial peeling force control layer (130), precisely control the peeling initiation position and progression path.
[0074] (2) Second blocking layer (122)
[0075] The second blocking layer (122) is a core blocking layer that performs an oxygen blocking function and can be formed on top of the first blocking layer (121), and can be formed as a composite structure in which plate-shaped inorganic particles are dispersed within a polymer matrix.
[0076] The second barrier layer (122) may include an ethylene-vinyl alcohol copolymer (EVOH), a polyamide (PA), and a polyvinyl alcohol (PVA), and preferably may be composed of 40 to 70 weight% EVOH, 10 to 30 weight% PA, and 10 to 30 weight% PVA. If the EVOH content is less than 40 weight%, sufficient oxygen barrier properties may not be ensured, and if it exceeds 70 weight%, a decrease in physical properties and an increase in brittleness may occur due to moisture absorption.
[0077] Plate-shaped inorganic particles may be dispersed in the second blocking layer (122), and the particles may include nano clay, graphene oxide, plate-shaped silica, or plate-shaped alumina.
[0078] The average thickness of the above-mentioned inorganic particles can be set to 10 to 200 nm, and the aspect ratio can be set to 10 to 500, preferably 20 to 200, and the content can be included in the range of 1 to 8 weight% based on 100 weight% of the total of the EVOH, PA, and PVA. If the particle content is less than 1 weight%, the effect of lengthening the gas transport path may be negligible, and if it exceeds 8 weight%, a gas permeation path may be formed instead due to aggregation between particles and the formation of aggregates. In addition, if the aspect ratio is less than 10, the effect of extending the blocking path may not be sufficiently secured.
[0079] The above particles can be surface-modified using a silane coupling agent or a polymer surfactant, which can improve dispersion stability within the polymer matrix. If such surface modification is not performed, particle aggregation occurs, forming local defects, which may lead to non-uniformity in oxygen barrier performance.
[0080] In the second blocking layer (122), the particles can be controlled to be aligned horizontally with respect to the film formation direction, and for this purpose, the shear force during co-extrusion can be maintained in the range of 10 to 100 s^-1. If the shear force is less than 10 s^-1, the alignment of the particles may not be sufficiently achieved, and if it exceeds 100 s^-1, particle breakage or matrix instability may occur.
[0081] Accordingly, the particle can perform the function of significantly reducing oxygen permeability by forming a tortuous path that non-linearly extends the gas movement path.
[0082] (3) Third blocking layer (123)
[0083] The third blocking layer (123) is a moisture blocking layer that suppresses the penetration of moisture and volatile components, and can be formed on top of the second blocking layer (122). It can be formed as a functional layer that forms a dense structure by controlling the degree of crystallization, molecular orientation, and free volume of the polymer matrix itself, rather than a blocking structure formed by particle dispersion. Accordingly, the third blocking layer (123) can perform a moisture blocking function in a manner distinct from the oxygen blocking function of the second blocking layer (122), and at the same time, can secure interfacial stability with the subsequently stacked fourth blocking layer (124).
[0084] The third barrier layer (123) may include PVDC (polyvinylidene chloride), PE (polyethylene), and PP (polypropylene), and preferably may be composed of 40 to 70 weight% PVDC, 10 to 30 weight% PE, and 10 to 30 weight% PP. If the content of the PVDC is less than 40 weight%, sufficient moisture barrier properties may not be secured, which may increase the possibility of the contents deteriorating due to the ingress of external moisture; if it exceeds 70 weight%, gel formation or local thermal decomposition may occur during the film formation process due to an increase in melt viscosity and a decrease in thermal stability. Additionally, if the content of the PE and PP is less than 10 weight% each, processability and elongation stability may decrease, and if it exceeds 30 weight%, the PVDC continuous phase may be weakened, and the moisture barrier path may become loose.
[0085] The third blocking layer (123) can be controlled so that its crystallinity is formed in the range of 35 to 75 percent with particles or beads substantially excluded. If the crystallinity is less than 35 percent, the free volume within the polymer matrix increases, which may increase the diffusion paths of moisture and volatile components, and if it exceeds 75 percent, the brittleness of the layer increases, which may cause microcracks during the lamination or peeling process.
[0086] The third barrier layer (123) can be controlled so that its molecular orientation index is in the range of 1.2 to 3.0. If the molecular orientation index is less than 1.2, the polymer chains may be arranged in a disordered manner and moisture barrier properties may not be sufficiently expressed, and if it exceeds 3.0, residual stress inside the layer may increase, causing cracks to occur during subsequent lamination processes or use.
[0087] The third blocking layer (123) can be formed by a co-extrusion process, and the extrusion temperature of the resin composition forming the third blocking layer (123) can be set to a range of 175 to 225 ℃. If the extrusion temperature is less than 175 ℃, the melting uniformity of the composition containing PVDC is not ensured, and thickness non-uniformity and interfacial defects may occur, and if it exceeds 225 ℃, the thermal decomposition or dehydrochlorination reaction of PVDC is promoted, which may result in color change of the film, microbubbles, and deterioration of blocking performance.
[0088] The melt viscosity of the third blocking layer (123) can be controlled to a range of 800 to 2500 Pa·s under the same shear rate conditions, and the viscosity ratio with the adjacent second blocking layer (122) and fourth blocking layer (124) can be maintained in a range of 0.7 to 1.5. If the viscosity ratio is less than 0.7, the third blocking layer (123) may flow excessively and form interfacial waviness, and if it exceeds 1.5, interfacial adhesion with adjacent layers may decrease, causing delamination or thickness variation between layers.
[0089] The third blocking layer (123) can be cooled through a cooling roll after passing through the die exit, and the surface temperature of the cooling roll can be controlled to a range of 15 to 45 ℃, and the cooling rate can be controlled to a range of 12 to 35 ℃ / sec. If the surface temperature of the cooling roll is less than 15 ℃ or the cooling rate exceeds 35 ℃ / sec, the amorphous region may be excessively fixed, and internal stress may increase; if it exceeds 45 ℃ or the cooling rate is less than 12 ℃ / sec, the crystal structure may become coarse, and the uniformity of the dense structure may decrease.
[0090] The third blocking layer (123) may undergo an annealing process at 50 to 110°C for 10 to 120 seconds after cooling. If the annealing temperature is less than 50°C or the time is less than 10 seconds, crystal structure stabilization may not be sufficiently achieved, and if the temperature exceeds 110°C or the time exceeds 120 seconds, brittleness may increase and interfacial stress may increase due to crystal overgrowth.
[0091] The thickness of the third blocking layer (123) may be formed in a range of 20 to 35% relative to the total thickness of the high blocking layer (120). If the thickness is less than 20%, the moisture blocking function may not be sufficiently expressed, and if it exceeds 35%, the overall rigidity of the layer increases, which may reduce the flexibility and peelability of the laminated structure.
[0092] The third barrier layer (123) can form a dense moisture barrier structure by controlling the composition, crystallinity, molecular orientation, free volume, viscosity, cooling condition, and annealing condition of the PVDC-based matrix in conjunction. Accordingly, the third barrier layer (123) can simultaneously secure excellent moisture barrier properties and stacking stability while preventing interfacial defects that may occur in a particle dispersion structure.
[0093] (4) 4th blocking layer (124)
[0094] The fourth blocking layer (124) is formed on top of the third blocking layer (123) and is a layer in contact with the interface peeling force control layer (130). It can be formed as a functional interface design layer that ensures durability against the external environment while simultaneously controlling the interface adhesion state and peeling initiation conditions. In particular, the fourth blocking layer (124) can be designed to simultaneously control surface energy and surface shape through a combined surface treatment structure rather than a single surface treatment, thereby maintaining a stable adhesion state during use while initiating uniform peeling under specific conditions. Additionally, the fourth blocking layer (124) is configured such that its thickness and the combined surface treatment effect are interconnected, allowing the penetration depth of the surface modification effect and the interface stress transfer characteristics to be controlled simultaneously.
[0095] The fourth blocking layer (124) may include PP (polypropylene), PE (polyethylene), and PU (polyurethane), and preferably may be composed of 40 to 70 weight% PP, 10 to 30 weight% PE, and 10 to 30 weight% PU. If the composition falls outside the above range, interfacial adhesion stability and peel control characteristics may be simultaneously degraded.
[0096] If the content of the above PP is less than 40 weight%, the structural strength and heat resistance of the fourth blocking layer (124) are reduced, and the surface structure formed during the composite surface treatment process may not be stably maintained, and consequently, the uniformity of the interfacial adhesion force may be reduced. On the other hand, if the content of the above PP exceeds 70 weight%, the elastic recovery force of the layer decreases and brittleness increases, so stress concentration occurs at the interface when an external force is applied, and uneven peeling or cracking may occur.
[0097] If the content of the above PE is less than 10 weight%, melt fluidity is reduced, and interfacial adhesion may not be sufficiently secured during the co-extrusion process, and it may be difficult to form uniform surface energy even after composite surface treatment. On the other hand, if the content of the above PE exceeds 30 weight%, interfacial adhesion increases excessively, which raises the critical stress for initiating peeling and may degrade the designed peeling trigger function.
[0098] If the content of the above PU is less than 10 weight%, the stress relaxation function at the interface is not sufficiently expressed, so stress concentration occurs in the adhesive state and peeling initiation may proceed unevenly. On the other hand, if the content of the above PU exceeds 30 weight%, the ductility of the layer increases excessively, causing deformation in response to external force to increase, and the contact area control effect formed by the composite surface treatment and micro-pattern structure decreases, which may result in an unstable peeling initiation position.
[0099] The surface of the fourth blocking layer (124) can be formed by a composite treatment method in which corona treatment, plasma treatment, and chemical surface modification are applied sequentially, and the treatment conditions can be controlled differentially according to the ratio of the thickness of the fourth blocking layer (124) to the total thickness of the high blocking layer (120).
[0100] When the thickness ratio of the fourth blocking layer (124) is in the range of 0.10 to 0.15 relative to the total thickness of the high blocking layer (120), the surface modification effect can be transmitted relatively quickly throughout the layer, so the corona treatment energy can be set in the range of 0.5 to 1.2 kW·min / m^2. On the other hand, when the thickness ratio of the fourth blocking layer (124) is increased to the range of 0.15 to 0.25 relative to the total thickness of the high blocking layer (120), the surface modification effect is difficult to transmit sufficiently to the interface, so the corona treatment energy can be increased to the range of 1.0 to 2.0 kW·min / m^2 to secure the surface activation depth.
[0101] Subsequently, plasma treatment can be performed in an oxygen or nitrogen atmosphere under power conditions of 50 to 300 W, and the treatment time can also be adjusted according to the thickness ratio of the fourth blocking layer (124). If the thickness ratio of the fourth blocking layer (124) is in the range of 0.10 to 0.15 relative to the total thickness of the high blocking layer (120), the treatment can be performed in the range of 1 to 5 sec, and if the thickness ratio is in the range of 0.15 to 0.25, the treatment can be set in the range of 5 to 10 sec. By differentially controlling the plasma treatment time according to the thickness ratio as described above, the formation depth of the surface roughness structure and the interfacial stress transfer characteristics can be balanced. When the thickness ratio is low, excessive plasma treatment may affect the interior of the layer and cause surface embrittlement or microcracks, so the treatment time needs to be limited; conversely, when the thickness ratio is high, a relatively long treatment time may be required for sufficient surface structure formation and interfacial activation.
[0102] Subsequently, chemical surface modification can be performed using a silane coupling agent or an isocyanate-based treatment agent, and the treatment concentration and reaction time can also be adjusted according to the thickness ratio of the fourth blocking layer (124).
[0103] When the thickness ratio of the fourth blocking layer (124) is in the range of 0.10 to 0.15 relative to the total thickness of the high blocking layer (120), the treatment concentration is set to 0.1 to 0.8 weight% and the treatment time is set to 5 to 30 sec, thereby preventing the formation of an excessive reaction layer and suppressing the excessive diffusion of surface modification into the interior of the layer. On the other hand, when the thickness ratio is in the range of 0.15 to 0.25, the treatment concentration is set to 0.8 to 2.0 weight% and the treatment time is set to 30 to 60 sec, thereby forming a sufficient chemical bond up to the interface and stably securing interfacial adhesion.
[0104] By controlling the thickness ratio of the fourth blocking layer (124), plasma treatment conditions, and chemical surface modification conditions in conjunction, the surface modification depth, interfacial bonding strength, and peeling initiation characteristics can be precisely controlled simultaneously.
[0105] As described above, when the thickness ratio of the fourth blocking layer (124) and the composite surface treatment conditions are designed in conjunction, the depth of modification to the interior of the layer, the interfacial stress transfer path, and the peeling initiation location can be controlled simultaneously beyond simple surface modification, and accordingly, interfacial non-uniformity and peeling deviation that may occur in a multilayer structure can be effectively suppressed.
[0106] A micro-pattern structure may be formed on the surface of the fourth blocking layer (124), and the pattern may be formed in a structure in which protrusions and non-contact portions are arranged in an alternating manner. The micro-pattern may include circular hemispherical protrusions and elliptical hemispherical protrusions, and the protrusions may be formed in a structure in which they are repeatedly arranged in a mixed form of a lattice arrangement and a hexagonal close-packed arrangement. The circular protrusions may be included in a ratio of 0.30 to 0.70 relative to the total number of protrusions, and the elliptical hemispherical protrusions may be included in a ratio of 0.30 to 0.70 relative to the total number of protrusions. If the ratio of the circular protrusions is less than 0.30, the isotropic stress dispersion effect is insufficient, and stress concentration may occur in a specific direction; if it exceeds 0.70, it becomes difficult to control the directionality of the pattern, and the control precision of the peeling initiation position may be reduced. If the ratio of the elliptical hemispherical protrusions is less than 0.30, the directional stress control effect is negligible, making it difficult to induce the peeling path; if it exceeds 0.70, stress may be concentrated in a specific direction, leading to localized peeling or non-uniform interfacial separation. The arrangement structure of the protrusions may be formed as a structure in which a lattice arrangement and a hexagonal close-packed arrangement are repeatedly arranged. The lattice arrangement may be formed at a ratio of 0.20 to 0.60 relative to the total arrangement area, and the hexagonal close-packed arrangement may be formed at a ratio of 0.40 to 0.80. If the ratio of the lattice arrangement is less than 0.20, the regularity of the spacing between patterns is insufficient, which may result in non-uniform interfacial stress transmission; if it exceeds 0.60, the effect of reducing the contact area is limited, which may degrade the peeling initiation control function.
[0107] If the ratio of the hexagonal dense array is less than 0.40, the filling efficiency between protrusions is reduced, and the stress dispersion effect relative to the contact area may decrease; if it exceeds 0.80, local stress concentration and interference between protrusions may occur due to the excessive dense structure. As described above, by simultaneously controlling the mixing ratio of circular protrusions and elliptical hemispherical protrusions and the mixing ratio of the grid array and the hexagonal dense array, isotropic stress dispersion and directional stress control can be simultaneously achieved on the surface of the fourth blocking layer (124), and accordingly, the stress transfer path at the interface can be precisely controlled to simultaneously secure uniform peeling initiation and a stable adhesion state.
[0108] If the size of the above pattern is less than 5 μm, the effect of reducing the contact area is negligible, so the peeling control function may not be sufficiently expressed, and if it exceeds 50 μm, interfacial defects and stress concentration may occur due to increased surface roughness. In addition, if the contact area ratio is less than 20 percent, separation may occur during use due to insufficient adhesion, and if it exceeds 80 percent, the peeling initiation control function may be degraded as it becomes similar to the overall adhesive structure.
[0109] The above pattern can be formed by a heat-pressure method using an embossing roll, and the roll temperature can be controlled to a range of 80 to 140 ℃, the pressure to a range of 2 to 10 MPa, and the contact time to a range of 0.1 to 2 sec. If the pressure is less than 2 MPa, pattern formation may be insufficient, and if it exceeds 10 MPa, film deformation and increased internal stress may occur.
[0110] The above-described pattern structure can selectively reduce the contact area while maintaining sufficient local adhesion, thereby controlling stress concentration at the interface and inducing uniform peeling initiation. In particular, circular or elliptical patterns are structures that uniformly disperse stress distribution and have the advantage of minimizing deviations along the peeling direction compared to linear patterns.
[0111] The thickness of the fourth blocking layer (124) can be formed in a range of 10 to 25 percent, preferably 12 to 20 percent, relative to the total thickness of the high blocking layer (120), and the thickness can act as a critical variable directly related to the penetration depth of the composite surface treatment effect and the interfacial stress transfer characteristics. If the thickness is less than 10 percent, the surface modification effect acts excessively on the entire layer, which may cause embrittlement and microcracks, and if it exceeds 25 percent, the surface treatment effect may not be sufficiently transmitted to the interface, which may degrade the peeling initiation control function.
[0112] The above-mentioned fourth blocking layer (124) can precisely control interfacial adhesion and peeling initiation conditions simultaneously by controlling the composition, composite surface treatment process, surface energy, surface roughness, micro-pattern structure, contact ratio, and thickness in conjunction. Accordingly, the above-mentioned fourth blocking layer (124) can go beyond a simple protective layer and simultaneously improve the stability of film usage and peeling control performance.
[0113] The above-mentioned high-barrier layer (120) can act as a functional layer that blocks the penetration of oxygen, moisture, and volatile components, while simultaneously controlling interfacial stress and energy distribution to ensure uniform peeling behavior. In particular, by designing the physical properties, thickness, and interfacial characteristics of each barrier layer within a multilayer structure to be interconnected, it can perform an integrated function that simultaneously secures barrier performance and peeling control performance.
[0114] <Interfacial peeling force control layer (130)>
[0115] The above-mentioned interface peeling force control layer (130) is interposed between the high-barrier layer (120) and the protective layer (140) and is formed to solve the problem of local fracture or uneven peeling occurring when interface stress is concentrated at a specific point during peeling due to the high density and rigidity of the high-barrier layer (120). It can perform the function of eliminating deviations in the peeling initiation position and ensuring that peeling propagation proceeds continuously at a constant speed by controlling the energy release rate at the interface to be uniformly distributed across the entire plane, rather than simply reducing the interface adhesive force. In particular, the above-mentioned interface peeling force control layer (130) is formed as a multilayer structure designed to separately control the peeling initiation, stress relief, propagation path, and terminal position in different layers, thereby fundamentally improving the problems of local peeling, tearing, and residue generation that occur in conventional structures relying on a single adhesive layer.
[0116] The above interface peel force control layer (130) can be laminated in the order of a first interface adhesion control layer (131) - a second stress buffer layer (132) - a third peel induction layer (133) - a fourth protective fusion layer (134).
[0117] The first interface adhesion control layer (131) is a layer in direct contact with the high barrier layer (120) and can perform the function of uniformly forming interface adhesion energy so that peeling initiation occurs uniformly across the entire surface without being concentrated at a specific point, and may include butyl acrylate-methyl methacrylate copolymer, polyester-based thermoplastic polyurethane (TPU), polydimethylsiloxane (PDMS) modified acrylic resin, and maleic anhydride grafted polypropylene (PP-g-MA).
[0118] When the content of the butyl acrylate-methyl methacrylate copolymer is less than 42% by weight, there is a problem of premature peeling occurring without external force due to insufficient interfacial adhesion, and when it exceeds 50% by weight, there is a problem of localized fracture occurring where the initiation of peeling is concentrated at a specific point due to excessive increase in interfacial adhesion.
[0119] When the content of the above polyester-based thermoplastic polyurethane (TPU) is less than 20% by weight, there is a problem in that the elasticity and interfacial compliance are insufficient, and stress concentration due to interfacial irregularities is not relieved, and when it exceeds 27% by weight, the entire layer becomes excessively softened, resulting in an uneven distribution of interfacial energy and an unstable peeling initiation location.
[0120] When the content of the above polydimethylsiloxane (PDMS) modified acrylic resin is less than 8% by weight, there is a problem in that the surface energy reduction and flattening effects are insufficient, causing the peel initiation force to vary by location, and when it exceeds 12% by weight, the interfacial adhesion force decreases rapidly, so continuous peel propagation does not occur and slip occurs.
[0121] When the content of the maleic anhydride grafted polypropylene (PP-g-MA) is less than 15% by weight, the phase separation structure within the layer is not sufficiently formed, resulting in insufficient formation of the interfacial energy gradient. When the content exceeds 25% by weight, the non-polar component increases excessively, leading to a decrease in interfacial adhesion with the high barrier layer (120).
[0122]
[0123] (2) Second stress buffer layer (132)
[0124] The second stress buffer layer (132) is a layer that relieves stress concentration occurring during peel propagation and controls the energy transfer rate to maintain peel propagation at a constant level, and may comprise 36 to 46 weight% of thermoplastic polyurethane (TPU), 24 to 30 weight% of styrene-ethylene-butylene-styrene (SEBS), 14 to 20 weight% of low-density polyethylene (LDPE), and 10 to 16 weight% of ethylene-propylene rubber (EPR).
[0125] If the content of the above polyester-based thermoplastic polyurethane (TPU) is less than 36 weight%, there is a problem in that stress buffering ability is insufficient, so stress concentration is transmitted directly during delamination propagation, causing rapid fracture, and if it exceeds 46 weight%, the entire layer becomes excessively softened, causing delamination propagation to be delayed or proceed discontinuously.
[0126] When the content of the above styrene-ethylene-butylene-styrene (SEBS) is less than 24% by weight, there is a problem that the elastic recovery force is insufficient and repetitive stress distribution is not performed smoothly, and when it exceeds 30% by weight, the viscoelastic properties of the layer increase excessively, causing deformation to accumulate and propagation stability to decrease during peeling.
[0127] If the content of the above low-density polyethylene (LDPE) is less than 14% by weight, there is a problem that the stress is not distributed uniformly due to insufficient fluidity within the layer, and if it exceeds 20% by weight, there is a problem that the mechanical strength is reduced and deformation or tearing of the layer itself occurs during the peeling process.
[0128] When the content of the above ethylene-propylene rubber (EPR) is less than 10% by weight, there is a problem in that the impact is not mitigated during delamination propagation due to insufficient deformation absorption capacity between interfaces, and when it exceeds 16% by weight, there is a problem in that the delamination propagation path becomes unstable due to excessive elasticity.
[0129] (3) Third peeling induction layer (133)
[0130] The third peel-inducing layer (133) is a layer that induces the peel propagation path to be maintained constant so that the peel leading edge proceeds stably, and may comprise 40 to 50 weight% isotactic polypropylene (i-PP), 24 to 30 weight% high-density polyethylene (HDPE), 8 to 12 weight% paraffin wax modified polypropylene, and 2 to 5 weight% erucamide-based release agent.
[0131] When the content of the above isotactic polypropylene (i-PP) is less than 40% by weight, there is a problem that the delamination path is dispersed due to a lack of crystalline-based propagation directionality, and when it exceeds 50% by weight, there is a problem that cracks occur irregularly during delamination due to increased brittleness.
[0132] If the content of the above high-density polyethylene (HDPE) is less than 24% by weight, there is a problem with the peeling tip shaking due to insufficient propagation stability, and if it exceeds 30% by weight, there is a problem with the peeling path spreading widely due to excessive flexibility.
[0133] If the content of the above paraffin wax modified polypropylene is less than 8% by weight, there is a problem that the interfacial friction reduction effect is insufficient and peel resistance increases, and if it exceeds 12% by weight, there is a problem that the interfacial adhesion is excessively reduced and peel propagation is not controlled.
[0134] If the content of the above erucamide-based release agent is less than 2% by weight, there is a problem that peeling initiation and propagation are not smooth, and if it exceeds 5% by weight, interfacial adhesion stability is reduced, and there is a problem that interlayer separation occurs unintentionally during the peeling process.
[0135] (4) 4th protective fusion layer (134)
[0136] The above-mentioned fourth protective fusion layer (134) is a layer that secures adhesion with the protective layer (140) and fixes the peel end position so that the peel interface does not change, and may comprise 30 to 40 weight% of ethylene-vinyl acetate copolymer (EVA), 24 to 32 weight% of methacrylic acid modified polypropylene (MAA-g-PP), 18 to 26 weight% of thermoplastic polyurethane-based hot-melt resin (TPU hot-melt), and 10 to 16 weight% of polymethyl methacrylate (PMMA)-based acrylic adhesive resin.
[0137] If the content of the above ethylene-vinyl acetate copolymer (EVA) is less than 30% by weight, there is a problem that the initial adhesion with the protective layer (140) is insufficient and the peeling end position becomes unstable, and if it exceeds 40% by weight, the entire layer becomes excessively softened and the peeling end interface becomes disordered.
[0138] If the content of the above methacrylic acid modified polypropylene (MAA-g-PP) is less than 24% by weight, there is a problem that the interfacial bonding strength due to the introduction of polar groups is insufficient, and the adhesive stability with the protective layer (140) is reduced, and if it exceeds 32% by weight, there is a problem that the interlayer cohesion strength becomes uneven due to excessive polarity.
[0139] If the content of the above thermoplastic polyurethane-based hot-melt resin (TPU hot-melt) is less than 18% by weight, there is a problem that the adhesive interface is not sufficiently formed during heat fusion, resulting in reduced adhesive strength, and if it exceeds 26% by weight, there is a problem that residue is generated during peeling due to excessive tackiness.
[0140] If the content of the above polymethyl methacrylate (PMMA)-based acrylic adhesive resin is less than 10% by weight, there is a problem that the interfacial fixing force is insufficient and the peel end position shifts, and if it exceeds 16% by weight, the rigidity of the layer increases and cracks occur during peeling.
[0141] The above interface peeling force control layer (130) can be formed by combining a co-extrusion process and a selective adhesive pattern application process, and the first to third layers (131 to 133) can be formed integrally by a multilayer co-extrusion process, and then the process may include selectively applying an adhesive to the interface between the third peeling inducing layer (133) and the fourth protective fusion layer (134). At this time, the adhesive may not be formed continuously on the front surface of the film, but may be applied in the form of a discontinuous pattern having an intentionally separated structure so that there are areas where the adhesive is not applied, thereby forming a difference in adhesive force across the entire interface and uniformly controlling the distribution of the energy release rate.
[0142] The above discontinuous pattern can be formed in at least one of a dot array pattern, a linear pattern, and a grid pattern.
[0143] The dot pattern is a structure in which adhesive application points with a diameter of 10 to 200 μm are arranged at regular intervals. Each dot forms an independent adhesive area, which has the advantage of allowing peeling initiation to occur dispersed across the entire surface, and in particular, it can improve initial peeling stability by minimizing local stress concentration. If the area occupancy of the dot pattern is less than 20%, there is a problem of reduced interfacial adhesive stability due to insufficient adhesive area, and if it exceeds 60%, the adhesive layer effectively becomes a continuous structure, causing peeling initiation to be concentrated at a specific point.
[0144] The line pattern is a structure in which linear adhesive layers with a width of 20 to 150 μm are arranged at regular intervals. By being positioned parallel or perpendicular to the direction of peeling, it can perform the function of inducing a peeling propagation path and has the advantage of improving peeling stability in a certain direction. If the area occupancy of the line pattern is less than 25%, there is a problem that the peeling path becomes irregular due to insufficient propagation path induction effect, and if it exceeds 70%, there is a problem that the adhesive area increases excessively, leading to increased peeling resistance.
[0145] The grid pattern is a structure in which intersecting linear patterns are repeatedly formed, and it has the advantage of forming a uniform adhesive force distribution across the entire film direction and ensuring that the initiation and propagation of peeling are not affected by directionality. If the area occupancy of the grid pattern is less than 30%, there is a problem of localized peeling occurring due to insufficient interfacial adhesion uniformity, and if it exceeds 75%, it transitions into a structure close to a continuous film, resulting in a problem of reduced peeling initiation uniformity.
[0146] In addition, the adhesive may comprise 38 to 48 weight% of an acrylic resin, 18 to 26 weight% of a polyurethane resin, 6 to 12 weight% of a silicone-modified resin, and 12 to 22 weight% of a polyolefin resin, and the composition ratio is a range to simultaneously ensure adhesive stability and peelability, and if each component falls outside the above range, problems such as uneven interfacial adhesion or unstable peeling behavior may occur.
[0147] The above adhesive application process can be performed under conditions of an application temperature of 40 to 80°C, an application pressure of 0.05 to 0.3 MPa, and a relative humidity of 30 to 60%. If the conditions fall outside these ranges, changes in adhesive viscosity, pattern bleeding, or interfacial defects may occur, resulting in a problem where the discontinuous pattern shape is not maintained.
[0148] As such, it is distinguished from conventional continuous adhesive layer structures in that the shape, area occupancy, and adhesive composition of the discontinuous pattern are designed to be interconnected, thereby forming a uniform difference in adhesive force across the entire interface and simultaneously controlling the initiation and propagation of peeling.
[0149] <Protection layer (140)>
[0150] The above protective layer (140) is formed on the upper surface of the interface peeling force control layer (130) to protect the film surface from the external environment and can function as a functional layer to prevent surface damage, tearing, and non-uniform breakage that occur during the peeling process. The above protective layer (140) is formed as a multilayer structure including a first protective layer (141), a second protective layer (142), and a third protective layer (143) rather than a single layer, and each layer is designed to have different mechanical properties and surface characteristics, thereby simultaneously securing external protection and peeling stability.
[0151] 1. First protective layer (141)
[0152] The first protective layer (141) is a layer that comes into direct contact with the interfacial peeling force control layer (130), and can ensure interfacial stress relief and adhesive stability.
[0153] The first protective layer (141) may comprise 45 to 60 weight% of polycarbonate-based thermoplastic polyurethane (PC-TPU), 20 to 30 weight% of polybutylene terephthalate (PBT), and 10 to 20 weight% of glycidyl methacrylate (GMA) modified epoxy resin.
[0154] If the content of the above polycarbonate-based thermoplastic polyurethane (PC-TPU) is less than 45 weight%, there is a problem in that the elasticity and interfacial compliance are insufficient, and stress concentration due to fine irregularities on the lower interface is not relieved, and if it exceeds 60 weight%, the entire layer becomes excessively softened, which reduces mechanical support and may cause deformation to concentrate due to external forces.
[0155] If the content of the above polybutylene terephthalate (PBT) is less than 20 weight%, there is a problem of reduced durability against repeated loads due to insufficient structural strength, and if it exceeds 30 weight%, the stiffness of the layer increases, which reduces the difference in physical properties with the lower interface and may reduce the stress distribution effect.
[0156] If the content of the above glycidyl methacrylate (GMA) modified epoxy resin is less than 10% by weight, interfacial adhesion stability is insufficient, and delamination may occur during long-term use, and if it exceeds 20% by weight, the degree of curing increases excessively, leading to increased brittleness and cracking.
[0158] 2. Second protective layer (142)
[0159] The second protective layer (142) is a layer formed on top of the first protective layer (141) and can act as a structural reinforcement layer that secures surface hardness, scratch resistance, and wear resistance, while dispersing local loads caused by external friction or impact and suppressing the occurrence and propagation of cracks in the coating layer. In particular, the second protective layer (142) may have a structure in which a high-hardness acrylic and polyurethane acrylate composite matrix and a functional inorganic filler with a multilayer core-shell structure are compositely designed to simultaneously secure mechanical strength and provide stress dispersion functions.
[0160] The second protective layer (142) may include a methyl methacrylate (MMA)-based acrylic resin, a butyl acrylate (BA) copolymer acrylic resin, an HDI or IPDI-based aliphatic polyurethane acrylate resin, and a silica (SiO₂)-based functional inorganic filler, and preferably may include 30 to 50 weight% of MMA-based acrylic resin, 10 to 20 weight% of BA copolymer acrylic resin, 15 to 25 weight% of HDI or IPDI-based aliphatic polyurethane acrylate resin, and 10 to 25 weight% of a silica (SiO₂)-based functional inorganic filler.
[0161] The above-mentioned functional inorganic filler has a core-shell structure, and by anisotropically orienting this core-shell inorganic filler, it can be formed into a structure that disperses stress transfer paths in stages. Accordingly, it can perform the function of alleviating stress concentration during the process in which local loads generated on the surface are transferred inward.
[0162] The above MMA-based acrylic resin is a high-hardness resin with a Tg of 90°C or higher that can serve to ensure surface hardness and scratch resistance, while the BA copolymer acrylic resin can alleviate stress generated during external impact by providing flexibility. In addition, the above HDI or IPDI-based aliphatic polyurethane acrylate resin can simultaneously secure hardness and impact resistance by forming a three-dimensional network after curing.
[0163] The functional inorganic filler included in the second protective layer (142) may not simply be uniformly dispersed, but may form an anisotropic dispersion structure arranged to have a specific directionality within the layer. Specifically, the inorganic filler may be distributed to be oriented in a vertical direction along the thickness direction of the film or in an inclined direction having a certain angle, thereby controlling the transmission and dispersion of loads applied from the outside in a specific direction. Due to this anisotropic dispersion structure, local stress concentrations occurring in a simple random dispersion structure are effectively suppressed, and the load is distributed throughout the layer, thereby achieving the effect of delaying crack occurrence and propagation. In particular, when the inorganic filler is oriented in a vertical direction, it can effectively transmit the compressive load applied to the film surface to the lower layer while mitigating stress concentration at the interface, and when oriented in an inclined direction, resistance to shear stress is improved, further enhancing durability against scratches and wear.
[0164] Preferably, the functional inorganic filler is a composite inorganic particle having a multilayer core-shell structure, and may include a core, a first shell (shell-1), a second shell (shell-2) and a third shell (shell-3), and may include 35-45% by weight of the core, 15-20% by weight of the first shell, 20-25% by weight of the second shell, and 15-20% by weight of the third shell based on 100% by weight of the total functional inorganic filler.
[0165] The above core may comprise 60 to 70 weight percent of spherical silica and 30 to 40 weight percent of ceria (CeO₂) based on 100 weight percent of the total core. The spherical silica forms a load-bearing framework to secure mechanical strength, while the ceria performs functions of blocking ultraviolet rays and inhibiting yellowing to improve photostability. If the content of spherical silica is less than 60 weight percent, structural strength may be insufficient, and if it exceeds 70 weight percent, optical balance may be reduced. If the content of ceria is less than 30 weight percent, the photostability effect may be insufficient, and if it exceeds 40 weight percent, optical turbidity may increase.
[0166] The first shell may comprise 45 to 55 weight percent boehmite (AlOOH) and 45 to 55 weight percent zirconium phosphate (ZrP) based on 100 weight percent of the total first shell. Boehmite improves interfacial bonding strength with the resin, and zirconium phosphate provides a mechanical reinforcement effect through a plate-like structure, thereby improving structural stability against impact loads. If the boehmite content is less than 45 weight percent, interfacial bonding strength may be insufficient, and if it exceeds 55 weight percent, moisture sensitivity may increase. If the zirconium phosphate content is less than 45 weight percent, the reinforcement effect may be insufficient, and if it exceeds 55 weight percent, the shell stiffness may increase excessively, leading to stress concentration.
[0167] The second shell may comprise 40 to 50 weight percent of hollow silica and 50 to 60 weight percent of hexagonal boron nitride (h-BN) based on 100 weight percent of the total second shell. The hollow silica performs a stress relief function by absorbing external impact energy through its internal pore structure, and the h-BN can improve wear resistance by dispersing frictional loads through its layered structure. If the hollow silica is less than 40 weight percent, the stress dispersion effect may be insufficient, and if it exceeds 50 weight percent, the shell strength may decrease. If the h-BN is less than 50 weight percent, wear resistance may be insufficient, and if it exceeds 60 weight percent, interlayer stress imbalance may occur.
[0168] The third shell comprises 45 to 55 weight percent of polymethylsilsesquioxane (PMSSQ) and 45 to 55 weight percent of nanodiamonds based on 100 weight percent of the total third shell, wherein the sum of the two components can be adjusted to be 100 weight percent, and PMSSQ can improve sliding characteristics by reducing the surface friction coefficient, and nanodiamonds can suppress the occurrence of surface scratches through high hardness. If PMSSQ is less than 45 weight percent, the friction reduction effect may be insufficient, and if it exceeds 55 weight percent, the hardness may decrease. If nanodiamonds are less than 45 weight percent, the hardness improvement effect may be insufficient, and if it exceeds 55 weight percent, surface defects may increase due to particle aggregation.
[0169] The functional inorganic filler with a multilayer core-shell structure as described above can simultaneously improve surface durability, scratch resistance, and wear resistance by having each layer work in combination to provide load support and light stability in the core, perform interfacial bonding and structural reinforcement in the first shell, perform impact energy absorption and frictional load distribution in the second shell, and reduce surface friction and improve hardness in the third shell.
[0170] The second protective layer (142) may include an inorganic filler with an average particle size of 50 to 300 nm based on D50, and if it falls outside this range, dispersion stability may be reduced or optical properties may be degraded due to increased surface roughness. Additionally, the second protective layer (142) may have a surface hardness of H to 3H based on pencil hardness, and the haze increase rate may be maintained at 5% or less after 1,000 abrasions in the ASTM D4060 Taber abrasion test.
[0171] (3) Third protective layer (143)
[0172] The third protective layer (143) is the outermost layer formed on top of the second protective layer (142) and is directly exposed to the outer surface of the cosmetic container film. It can perform anti-fouling and easy-cleaning functions to suppress the attachment of oily contaminants such as finger contact, sebum, foundation, lip formulation, sunscreen, and silicone-based cosmetics during use, and to allow contaminants to be easily removed even if they are attached. Additionally, the third protective layer (143) can perform functions to suppress the wetting and diffusion of oil by reducing surface free energy and controlling the surface microstructure, and to reduce the residue of fingerprint marks or traces of cosmetic transfer.
[0173] The third protective layer (143) may comprise 25-40% by weight of fluorinated acrylic resin, 20-30% by weight of silicone resin, 15-25% by weight of urethane resin, and 15-30% by weight of functional antifouling additive, based on 100% by weight of the total.
[0174] The above fluorinated acrylic resin may include a fluoroalkyl methacrylate copolymer containing perfluoroalkyl groups, and the number of carbon atoms in the fluoroalkyl groups may be in the range of C6 to C12. The above fluorinated acrylic resin can lower the surface free energy of the coating layer to reduce the wettability of oils and cosmetic ingredients.
[0175] The above silicone-based resin may include a polydimethylsiloxane (PDMS) modified resin or a silicone polyether copolymer, and may have the characteristic of migrating to the surface and rearranging after the formation of a coating layer due to the passage of time or external stimuli. Accordingly, dynamic surface rearrangement characteristics can be realized in which a low surface energy state is spontaneously recovered even if the surface is temporarily damaged by friction or contamination.
[0176] The above urethane-based resin may include aliphatic polyurethane or urethane acrylate resin, and by imparting flexibility and impact resistance to the outermost layer, it can suppress the occurrence of microcracks caused by repeated contact and friction and improve the maintenance of surface function during long-term use.
[0177] The above-mentioned functional antifouling additive may include one or more selected from the group consisting of perfluoropolyether, polyhedral oligomeric silsesquioxane (POSS), poly(ionic liquid), hexagonal boron nitride nanosheet, MXene, and fluorinated graphene. The perfluoropolyether can perform the function of inhibiting the attachment of contaminants through its ultra-low surface energy characteristics, and the polyhedral oligomeric silsesquioxane can simultaneously improve surface hardness and stain resistance through an inorganic-organic hybrid structure. The poly(ionic liquid) can inhibit the attachment of contaminants or facilitate their removal by simultaneously forming hydrophilic and hydrophobic domains on the surface, and the hexagonal boron nitride nanosheet can perform the function of reducing friction and inhibiting the attachment of contaminants through its layered structure. In addition, the MXene or fluorinated graphene can provide a surface barrier effect through its two-dimensional plate-like structure and suppress the attachment and retention of contaminants.
[0178] Preferably, the functional antifouling additive may be a mixture comprising perfluoropolyether, polyhedral oligomeric silsesquioxane (POSS), poly(ionic liquid), hexagonal boron nitride nanosheet, MXene, and fluorinated graphene. The mixing ratio may be 15 to 30 weight% of perfluoropolyether, 10 to 25 weight% of polyhedral oligomeric silsesquioxane, 10 to 20 weight% of poly(ionic liquid), 10 to 20 weight% of hexagonal boron nitride nanosheet, 5 to 15 weight% of MXene, and 5 to 15 weight% of fluorinated graphene, when the total weight of the functional antifouling additive is 100.
[0179] The above-described functional antifouling additive is composed of a composite mixture comprising perfluoropolyether, polyhedral oligomeric silsesquioxane, a polyionic liquid, hexagonal boron nitride nanosheets, MXene, and fluorinated graphene. Its composition and technical concept are clearly distinguished from the simple mixture of fluorinated resins, silicone resins, and inorganic particles commonly used in the field of conventional antifouling coatings. In particular, each of the above components is selected to perform functions that do not overlap with one another; the perfluoropolyether inhibits the adhesion of contaminants by reducing surface free energy, the polyhedral oligomeric silsesquioxane improves surface hardness and durability through an inorganic-organic hybrid structure, and the polyionic liquid controls the adhesion and removal behavior of contaminants by simultaneously forming hydrophilic and hydrophobic domains. Additionally, the hexagonal boron nitride nanosheets reduce friction through their layered structure, while MXene and fluorinated graphene provide surface barrier properties through their two-dimensional plate-like structures to inhibit the deposition and retention of contaminants.
[0180] If the content of the above-mentioned fluorine-based acrylic resin is less than 25% by weight, there is a problem in that the surface free energy reduction effect is insufficient and water and oil repellency against oil and cosmetic ingredients is not sufficiently secured, and if it exceeds 40% by weight, the brittleness of the entire layer increases, and cracks occur due to external friction or impact.
[0181] If the content of the above silicone-based resin is less than 20% by weight, the self-healing properties due to surface rearrangement are not sufficiently expressed, resulting in a decrease in anti-fouling performance; if it exceeds 30% by weight, the interfacial mobility increases excessively, resulting in a decrease in the mechanical strength of the coating layer.
[0182] If the content of the above urethane resin is less than 15% by weight, there is a problem in that it is difficult to suppress the occurrence of microcracks caused by repeated friction due to insufficient flexibility and impact resistance, and if it exceeds 25% by weight, the entire layer becomes excessively softened, resulting in a decrease in surface hardness and reduced scratch resistance.
[0183] If the content of the above functional antifouling additive is less than 15% by weight, there is a problem that non-adhesion to contaminants is not sufficiently ensured, and if it exceeds 30% by weight, there is a problem that the durability of the coating layer is reduced and performance retention is reduced during long-term use due to excessive surface migration of the additive.
[0185] The protective layer (140) may be formed by a coating or co-extrusion process, and in particular, the second protective layer (142) and the third protective layer (143) may be formed through a slot-die coating or gravure coating process. At this time, the coating temperature may be controlled to 50 to 120°C, the coating pressure to 0.05 to 0.4 MPa, and the relative humidity to 30 to 65%, and if the conditions fall outside these ranges, non-uniformity in the thickness of the coating layer, pinholes, or interface defects may occur. Additionally, the total thickness of the protective layer (140) may be formed in the range of 5 to 40 μm; if it is less than 5 μm, the protective function may not be sufficiently secured, and if it exceeds 40 μm, the flexibility of the entire film may be reduced, thereby limiting applicability.
[0186] As such, the above protective layer (140) has technical features that distinguish it from a simple protective layer in that it secures external protection and mechanical stability through a multilayer structure and composition control, while simultaneously performing an auxiliary function to maintain a uniform stress distribution during peeling through interaction with the lower interface peeling force control layer (130).
[0187] The above protective layer (140) is a functional outer layer formed on top of the interface peeling force control layer (130), and can be designed to simultaneously secure external protection function and peeling stability by utilizing the difference in physical properties of the multilayer structure, and can be formed as a multilayer structure in which the first protective layer (141), the second protective layer (142), and the third protective layer (143) are sequentially stacked. The manufacturing of the above protective layer (140) can be performed by a hybrid process combining a co-extrusion process and a precision coating process, and interlayer interface stability and surface functionality can be simultaneously secured by controlling the formation process conditions of each layer to be interconnected.
[0188] The first protective layer (141) can be formed on the upper surface of the interface peel force control layer (130) by a co-extrusion method, and the extrusion temperature can be controlled to a range of 180 to 240°C and the die pressure to a range of 5 to 15 MPa. If the extrusion temperature is less than 180°C, the melting uniformity of the resin is not ensured, which may result in interlayer adhesion failure, and if it exceeds 240°C, thermal decomposition of the resin and degradation of physical properties may occur. In addition, if the die pressure is less than 5 MPa, film adhesion is insufficient, which may result in interfacial voids, and if it exceeds 15 MPa, there is a problem of increased thickness variation due to excessive shear stress. The first protective layer (141) formed in this manner acts as a stress buffer layer with the lower interface peel force control layer (130) and can perform the role of smoothly controlling the transfer of interfacial stress.
[0189] Subsequently, the second protective layer (142) can be formed by a slot-die coating or gravure coating method, and the coating viscosity can be controlled in the range of 500 to 3000 mPa·s and the coating speed in the range of 10 to 80 m / min. If the coating viscosity is less than 500 mPa·s, the coating liquid diffuses excessively, making it difficult to control the thickness, and if it exceeds 3000 mPa·s, the coating uniformity is reduced and surface defects may occur. In addition, if the coating speed is less than 10 m / min, productivity is reduced, and if it exceeds 80 m / min, bubbles and streak defects may occur within the coating layer. After coating, a drying process can be performed at a drying temperature of 60 to 120°C for 10 to 60 seconds to remove the solvent and form a dense protective layer structure.
[0190] The third protective layer (143) above is the outermost layer and can be formed through a micro-coating or surface treatment process to impart surface functionality, and a plasma treatment or UV curing process may be performed in parallel. In the case of plasma treatment, the treatment power can be controlled to a range of 50 to 300 W and the treatment time to a range of 1 to 10 seconds, and if it falls outside the above range, surface activation may be insufficient or excessive surface deterioration may occur. In addition, the UV curing process can be performed with an irradiation dose of 200 to 1000 mJ / cm^2, and if the irradiation dose is less than 200 mJ / cm^2, durability may be reduced due to incomplete curing, and if it exceeds 1000 mJ / cm^2, surface embrittlement may occur.
[0191] Each of the above processes can be performed under environmental conditions of relative humidity of 30 to 65% and process temperature of 20 to 40°C, and if these conditions are not maintained, problems such as moisture condensation, surface defects, and interfacial non-uniformity may occur. In addition, the total thickness of the protective layer (140) can be precisely controlled within the range of 5 to 40 μm, and the thickness deviation can be controlled to be maintained within ±5%.
[0192] In this way, the protective layer (140) is formed through a multi-stage process combining co-extrusion and coating processes, and the formation conditions, viscosity, temperature, pressure, and surface treatment conditions of each layer are mutually linked and optimized, thereby having manufacturing technical features that differentiate it from a conventional single protective layer structure in that it simultaneously secures external protection functions as well as stress distribution and surface stability during the peeling process.
[0193] The above high-barrier film (100) can be laminated in the order of a first substrate layer (111), a second substrate layer (112), a third substrate layer (113), a first barrier layer (121), a second barrier layer (122), a third barrier layer (123), a fourth barrier layer (124), a first interface adhesion control layer (131), a second stress buffer layer (132), a third peel-inducing layer (133), a fourth protective fusion layer (134), and a protective layer (140) in the outer direction from the side of the container body. More specifically, the substrate layer (110) may have a structure in which a first substrate layer (111), a second substrate layer (112), and a third substrate layer (113) are sequentially stacked, and the high barrier layer (120) may have a structure in which a first barrier layer (121), a second barrier layer (122), a third barrier layer (123), and a fourth barrier layer (124) are sequentially stacked on top of the third substrate layer (113), and the interface peeling force control layer (130) may have a structure in which a first interface adhesion control layer (131), a second stress buffer layer (132), a third peeling induction layer (133), and a fourth protective fusion layer (134) are sequentially stacked on top of the fourth barrier layer (124). The protective layer (140) may be formed on top of the fourth protective fusion layer (134) and arranged to form the outermost layer. In this way, each layer is not simply stacked, but can form a stacked structure that is functionally interconnected so that mechanical support and stress transfer paths are established in the lower substrate layer (110), the penetration of oxygen, moisture, and volatile components is blocked in the middle high-barrier layer (120), the peeling initiation, peeling propagation, and peeling termination position are controlled in the upper interface peeling force control layer (130), and durability and surface stability against the external environment are secured in the outermost protective layer (140). Accordingly, the high-barrier film (100) can maintain container attachment stability and high barrier properties during the usage stage, while being peeled uniformly and reproducibly along the designed interface during the recycling stage.
[0194] The manufacturing of the above-described high-barrier film (100) may include a step of forming a substrate layer (110), a step of forming a high-barrier layer (120), a step of forming an interface peeling force control layer (130), and a step of forming a protective layer (140). First, a first substrate layer (111), a second substrate layer (112), and a third substrate layer (113) may be simultaneously laminated through a co-extrusion process to form a substrate layer (110). Subsequently, a first barrier layer (121), a second barrier layer (122), a third barrier layer (123), and a fourth barrier layer (124) may be sequentially formed on top of the substrate layer (110) using a co-extrusion or continuous co-extrusion method to laminate a high-barrier layer (120). Next, a first interface adhesion control layer (131), a second stress buffer layer (132), and a third peeling inducing layer (133) can be integrally formed on the upper part of the fourth barrier layer (124) by co-extrusion, and a protective fusion layer (134) can be laminated on the upper part by thermal fusion to form an interface peeling force control layer (130). Subsequently, a protective layer (140) can be formed on the upper part of the fourth protective fusion layer (134) by coating or co-extrusion to manufacture a final high barrier film (100). Preferably, the lamination process may be configured such that the process of forming the substrate layer (110) and the high barrier layer (120), the process of forming the high barrier layer (120) and the interface peeling force control layer (130), and the process of forming the interface peeling force control layer (130) and the protective layer (140) are performed on a continuous line, thereby minimizing interfacial contamination between layers and improving interlayer adhesion stability.
[0196] <Examples and Comparative Examples>
[0197] 1. Example 1
[0198] The substrate layer (110) was formed by a multilayer co-extrusion process, and the first substrate layer (111), the second substrate layer (112), and the third substrate layer (113) were simultaneously laminated using a multi-manifold T-die. At this time, the first substrate layer (111) was formed with a composition of PET 55 wt%, PP 20 wt%, and PA 25 wt%, the second substrate layer (112) was formed with a composition of EVOH 45 wt%, PU 30 wt%, and PE 25 wt%, and the third substrate layer (113) was formed with a composition of PC 45 wt%, PMMA 30 wt%, and PS 25 wt%. During co-extrusion, the extrusion temperature of the first substrate layer (111) was set to 255°C, the extrusion temperature of the second substrate layer (112) to 215°C, and the extrusion temperature of the third substrate layer (113) to 238°C. The melt viscosity of each layer was controlled to a range of 1200 to 1300 Pa·s under the same shear rate conditions, and the viscosity ratio between adjacent layers was maintained at 0.9 to 1.1. In addition, the extrusion pressure of each layer was controlled to a range of 108 to 112 bar so that the pressure deviation was 5 bar or less, and the flow rate deviation inside the co-extrusion die was maintained within ±3% for each layer. At the die exit, cooling was performed using a cooling roll at 35°C at a cooling rate of 22°C / sec, and the process was carried out in a nitrogen atmosphere to maintain the oxygen concentration at 0.5% or less.
[0199] Subsequently, the high barrier layer (120) was formed on the upper surface of the substrate layer (110) by a continuous co-extrusion process, the first barrier layer (121) was formed to include 47.5 wt% PE, 19 wt% PP, 28.5 wt% PU, and 5 wt% synthetic beads with an average particle size of 5 μm, the second barrier layer (122) was formed to include 4 wt% plate-shaped inorganic particles based on 100 wt% resin composition including 55 wt% EVOH, 20 wt% PA, and 25 wt% PVA, the third barrier layer (123) was formed with 55 wt% PVDC, 20 wt% PE, and 25 wt% PP, and the fourth barrier layer (124) was formed with 55 wt% PP, 20 wt% PE, and 25 wt% PU. At this time, the first to fourth blocking layers (121 to 124) are integrally laminated by a co-extrusion process without a separate adhesive layer.
[0200] The synthetic beads used were spherical polymethyl methacrylate (PMMA) beads with an average particle size of 5 μm. The synthetic beads were used with a surface treated with a silane coupling agent to improve interfacial affinity with the resin matrix.
[0201] The above plate-shaped inorganic particles used were plate-shaped nanoclay particles having an average thickness of 70 nm and an aspect ratio of 80. The above plate-shaped inorganic particles were prepared with their surfaces treated with an amine-based silane coupling agent.
[0202] At this time, the extrusion temperature of the first blocking layer (121) was set to 210°C, the extrusion temperature of the second blocking layer (122) to 205°C, the extrusion temperature of the third blocking layer (123) to 190°C, and the extrusion temperature of the fourth blocking layer (124) to 215°C. In particular, the third blocking layer (123) containing PVDC was controlled to 190°C so that it could be stably formed within the range of 175 to 225°C, and the melt viscosity was set to 1500 Pa·s under the same shear rate conditions, and the viscosity ratio between the second blocking layer (122) and the fourth blocking layer (124) was adjusted to 1.1 and 0.9, respectively. In addition, in the entire multilayer structure of the first blocking layer (121) to the fourth blocking layer (124), the viscosity ratio between adjacent blocking layers was controlled to be maintained in the range of 0.8 to 1.3, thereby ensuring interlayer flow stability while suppressing excessive occurrence of interfacial waveforms. If the viscosity ratio is less than 0.8, the interface boundary may become blurred, and if it exceeds 1.3, thickness variation and local delamination may occur due to interface shear instability. In addition, the laminate including the third barrier layer (123) is cooled at a cooling rate of 25°C / sec using a cooling roll at 30°C after passing through the die exit, and then heat-treated at 80°C for 60 seconds to stably form a dense moisture barrier structure. The heat treatment process is not for interlayer adhesion, but is a process for stabilizing the crystal structure and relieving residual stress.
[0203] Subsequently, the interface peeling force control layer (130) was formed by first integrally forming the first interface adhesion control layer (131), the second stress buffering layer (132), and the third peeling inducing layer (133) through a multilayer co-extrusion process, and then subsequently laminating the fourth protective fusion layer (134). At this time, the first interface adhesion controlling layer (131) is formed to comprise 46 wt% butyl acrylate-methyl methacrylate copolymer, 24 wt% polyester-based thermoplastic polyurethane (TPU), 10 wt% polydimethylsiloxane (PDMS) modified acrylic resin, and 20 wt% maleic anhydride grafted polypropylene (PP-g-MA); the second stress buffering layer (132) is formed to comprise 40 wt% thermoplastic polyurethane, 27 wt% styrene-based thermoplastic elastomer, 18 wt% low-density polyethylene, and 15 wt% ethylene-propylene rubber (EPR); and the third peel-inducing layer (133) is formed to comprise 45 wt% isotactic polypropylene (i-PP), 27 wt% high-density polyethylene, 10 wt% paraffin wax modified polypropylene, and an erucamide-based release agent. It was formed to contain 3 weight percent. The first to third layers (131 to 133) were controlled to have a melt viscosity in the range of 900 to 1800 Pa·s under the same shear rate conditions, and the viscosity ratio between adjacent layers was controlled to be maintained in the range of 0.85 to 1.25. In particular, by setting the viscosity ratio close to 1.0, the interfacial shear stress distribution was formed uniformly; if the viscosity ratio is less than 0.85, the collapse of the interfacial structure may occur due to interlayer flow imbalance, and if it exceeds 1.25, the peeling initiation location may become non-uniform due to increased interfacial wave shape. At this time, the interfacial bonding between the first to third layers (131 to 133) is also formed by interfacial diffusion in the molten state without an adhesive.
[0204] In addition, in the entire lamination process, the melt viscosity of each functional layer is controlled within the range of 800 to 2000 Pa·s, and the melt viscosity of the substrate layer (110), the high barrier layer (120), and the interface peeling force control layer (130) is set to be mutually linked within the above range. At this time, the bonding between each layer is formed by a thermal fusion method in which interface diffusion is induced by heat and pressure, rather than by an adhesive.
[0205] Subsequently, the fourth protective fusion layer (134) was formed to include 35% by weight of ethylene-vinyl acetate, 28% by weight of methacrylic acid-modified polypropylene (MAA-g-PP), 22% by weight of polyurethane-based heat-fusible resin, and 15% by weight of polymethyl methacrylate (PMMA)-based acrylic adhesive resin. The fourth protective fusion layer (134) is formed without a separate adhesive application process and is configured to be directly fused with an adjacent layer under heat and pressure conditions. Subsequently, the fourth protective fusion layer (134) is bonded with an adjacent layer through a heat fusion process without the application of a separate adhesive. Subsequently, the fourth protective fusion layer (134) was heat-fused under conditions of 105°C, 0.5 MPa, and 1.2 sec to secure interfacial bonding strength. Afterwards, a protective layer (140) with a total thickness of 18 μm was formed on top of the fourth protective fusion layer (134).
[0206] The adhesive was prepared with a composition of 44% by weight of acrylic resin, 22% by weight of polyurethane resin, 9% by weight of silicone-modified resin, and 20% by weight of polyolefin resin. It was applied in a discontinuous pattern mixed with dot and grid patterns using a slot die method under conditions of an application temperature of 60°C, an application pressure of 0.15 MPa, and a relative humidity of 45%, and the area occupancy rate was controlled to 48%. At this time, the adhesive was adjusted to have a viscosity of 1500 to 3000 cP under the application conditions to suppress pattern bleeding and connection phenomena and to maintain the designed pattern shape. Subsequently, a fourth protective fusion layer (134) was laminated and heat-fused under conditions of 105°C, 0.5 MPa, and 1.2 sec. Finally, a protective layer (140) with a total thickness of 18 μm was formed on top of the fourth protective fusion layer (134).
[0207] The substrate layer (110), high barrier layer (120), interface peel force control layer (130), and protective layer (140) formed as described above are integrated into a single laminated structure through continuous co-extrusion and subsequent lamination processes. Specifically, after forming the substrate layer (110), the high barrier layer (120) is continuously laminated on the same line using an inline co-extrusion method, and a multilayer feed block is used to allow direct lamination without interface separation. Subsequently, the interface peel force control layer (130) is laminated through a thermal compression process, and this process is performed as a dry process that does not use adhesive. The lamination temperature is controlled to 95 to 110°C, the pressure to 0.4 to 0.6 MPa, and the contact time to 1.0 to 1.5 s. Subsequently, the fourth protective fusion layer (134) is fixed by a thermal fusion process, and the protective layer (140) is formed by an extrusion coating method, with the die temperature controlled to 210 to 230°C, the lamination pressure to 0.5 to 0.8 MPa, and the cooling roll temperature to 25 to 35°C. At this time, the entire lamination process is performed as a process without using adhesive, and all interlayer bonding is formed by thermal fusion or melt diffusion. In addition, in the entire lamination process, the melt viscosity of each functional layer is set to be mutually linked within the range of 800 to 2000 Pa·s, and the interlayer viscosity ratio is controlled to be maintained within the range of 0.8 to 1.3, thereby forming a uniform distribution of energy release rate at the interface and stably controlling the peeling initiation and propagation behavior.
[0209] 2. Comparative Example 1
[0210] The substrate layer (110) is formed by a co-extrusion process, but instead of applying a functionally divided three-layer structure of the first substrate layer (111), second substrate layer (112), and third substrate layer (113) as in Example 1, it is formed as a simplified three-layer structure focused on mechanical strength.
[0211] Specifically, the first substrate layer (111) is formed with a composition of 75 wt% PET, 15 wt% PP, and 10 wt% PA, the second substrate layer (112) is formed with a composition of 65 wt% EVOH, 15 wt% PU, and 20 wt% PE, and the third substrate layer (113) is formed with a composition of 65 wt% PC, 20 wt% PMMA, and 15 wt% PS. At this time, the extrusion temperature of the first substrate layer (111) is set to 265°C, the extrusion temperature of the second substrate layer (112) is set to 228°C, and the extrusion temperature of the third substrate layer (113) is set to 248°C, and the melt viscosity of each layer is formed to be in the range of 1400 to 2100 Pa·s under the same shear rate conditions, and the viscosity ratio between adjacent layers is maintained at a level of 1.4 to 1.8.
[0212] In addition, the extrusion pressure of each layer was controlled to a range of 118 to 126 bar, and the flow rate deviation inside the co-extrusion die was set to ±5% for each layer. At the die exit, cooling was performed using a cooling roll at 28°C at a cooling rate of 18°C / sec.
[0213] In addition, the high barrier layer (120), the interface peeling force control layer (130), and the protective layer (140) were formed with the same composition and lamination conditions as in Example 1.
[0215] 3. Comparative Example 2
[0216] The substrate layer (110), the interfacial peeling force control layer (130), and the protective layer (140) are formed in the same manner as in Example 1, but only the high barrier layer (120) is formed differently. Specifically, the first barrier layer (121) is formed to include 65 wt% PE, 15 wt% PP, 20 wt% PU, and 1 wt% synthetic beads with an average particle size of 12 μm, the second barrier layer (122) is formed to include 70 wt% EVOH, 15 wt% PA, 15 wt% PVA, and 1 wt% plate-shaped inorganic particles, the third barrier layer (123) is formed to include 40 wt% PVDC, 30 wt% PE, and 30 wt% PP, and the fourth barrier layer (124) is formed to include 70 wt% PP, 15 wt% PE, and 15 wt% PU. At this time, the extrusion temperature of the first blocking layer (121) was set to 220°C, the extrusion temperature of the second blocking layer (122) to 214°C, the extrusion temperature of the third blocking layer (123) to 223°C, and the extrusion temperature of the fourth blocking layer (124) to 228°C. In particular, the third blocking layer (123) containing PVDC was formed at a temperature close to the upper limit to reduce the thermal stability margin, and the content of inorganic particles included in the second blocking layer (122) was also set low so that the bending path formation effect would not be sufficiently displayed. In addition, the viscosity ratio of each blocking layer was maintained at a level of 1.3 to 1.6 to form conditions in which interfacial ripple phenomena could occur partially.
[0217] After that, the interfacial peeling force control layer (130) and the protective layer (140) were laminated in the same line as in Example 1.
[0219] 4. Comparative Example 3
[0220] The substrate layer (110), the high barrier layer (120), and the protective layer (140) are formed in the same way as in Example 1, but the interface peeling force control layer (130) is formed differently.
[0221] The first interface adhesion control layer (131) is formed to include 52% by weight of acrylic resin, 18% by weight of polyurethane resin, 5% by weight of silicone-modified resin, and 25% by weight of polyolefin resin, the second stress buffering layer (132) is formed to include 48% by weight of thermoplastic polyurethane, 22% by weight of styrene-based thermoplastic elastomer, 12% by weight of low-density polyethylene, and 18% by weight of polyolefin-based elastomer, and the third peel-inducing layer (133) is formed to include 52% by weight of polypropylene, 22% by weight of high-density polyethylene, 14% by weight of wax-modified polyolefin, and 5% by weight of release agent.
[0222] The fourth protective fusion layer (134) was formed to include 42% by weight of ethylene-vinyl acetate, 22% by weight of methacrylic acid-modified polyolefin, 24% by weight of polyurethane-based hot melt resin, and 12% by weight of acrylic-based adhesive resin.
[0223] At this time, due to the change in composition of the first to third layers, the melt viscosity of each layer is formed in the range of about 800 to 2200 Pa·s under the same shear rate conditions, and the viscosity ratio between adjacent layers may be formed non-uniformly at a level of 0.6 to 1.8. This viscosity imbalance causes non-uniform stress transfer at the interface, resulting in excessive adhesion in certain areas and insufficient adhesion in other areas.
[0224] The adhesive was prepared with a composition of 48 wt% acrylic resin, 18 wt% polyurethane resin, 6 wt% silicone-modified resin, and 28 wt% polyolefin resin, and was applied in the form of a semi-continuous pattern with a high density of linear patterns using a slot die method under conditions of a coating temperature of 78°C, a coating pressure of 0.28 MPa, and a relative humidity of 58%, and the area occupancy rate was controlled to 74%.
[0225] In addition, under the above conditions, the adhesive is applied in a relatively low viscosity state, causing connections between patterns; consequently, the discontinuous pattern structure is not maintained, and a continuous adhesive region is formed across the entire interface.
[0226] Subsequently, a fourth protective fusion layer (134) was laminated and heat-fused under conditions of 118°C, 0.7 MPa, and 2.0 sec. Then, a protective layer (140) was laminated under the same conditions as in Example 1.
[0228] 5. Comparative Example 4
[0229] The substrate layer (110), the high barrier layer (120), and the protective layer (140) are formed in the same way as in Example 1, but the interface peeling force control layer (130) is formed differently.
[0230] The first interface adhesion control layer (131) is formed to include 52% by weight of acrylic resin, 18% by weight of polyurethane resin, 5% by weight of silicone-modified resin, and 25% by weight of polyolefin resin, the second stress buffering layer (132) is formed to include 48% by weight of thermoplastic polyurethane, 22% by weight of styrene-based thermoplastic elastomer, 12% by weight of low-density polyethylene, and 18% by weight of polyolefin-based elastomer, and the third peel-inducing layer (133) is formed to include 52% by weight of polypropylene, 22% by weight of high-density polyethylene, 14% by weight of wax-modified polyolefin, and 12% by weight of release agent. The fourth protective fusion layer (134) was formed to include 42% by weight of ethylene-vinyl acetate, 22% by weight of methacrylic acid-modified polyolefin, 24% by weight of polyurethane-based hot melt resin, and 12% by weight of acrylic-based adhesive resin.
[0231] At this time, due to the change in composition of the first to third layers, the melt viscosity of each layer is formed in the range of about 800 to 2200 Pa·s under the same shear rate conditions, and the viscosity ratio between adjacent layers may be formed non-uniformly at a level of 0.6 to 1.8. This viscosity imbalance causes non-uniform stress transfer at the interface, resulting in excessive adhesion in certain areas and insufficient adhesion in other areas.
[0232] The adhesive was prepared with a composition of 48 wt% acrylic resin, 18 wt% polyurethane resin, 6 wt% silicone-modified resin, and 22 wt% polyolefin resin, and was applied in the form of a semi-continuous pattern with a high density of linear patterns using a slot die method under conditions of a coating temperature of 78°C, a coating pressure of 0.28 MPa, and a relative humidity of 58%, and the area occupancy rate was controlled to 74%.
[0233] In addition, under the above conditions, the adhesive is applied in a relatively low viscosity state, causing connections between patterns; consequently, the discontinuous pattern structure is not maintained, and a continuous adhesive region is formed across the entire interface.
[0234] Subsequently, a fourth protective fusion layer (134) was laminated and heat-fused under conditions of 118°C, 0.7 MPa, and 2.0 sec. Then, a protective layer (140) was laminated under the same conditions as in Example 1.
[0235] division Viscosity range (Pa·s) Interlayer viscosity ratio Interface state OTR (cc / m²·day) WVTR (g / m²·day) 180° peel strength (N / 25mm) Peeling deviation (%) evaluation Example 1 900~1800 0.8~1.3 Interfacial stability, no waveform 3.2 2.1 2.4 ±6 standard Comparative Example 1 1400~2100 1.4~1.8 Interfacial waveform formation, increased thickness variation 4.8 3.6 2.9 ±18 Instability of the base layer Comparative Example 2 800~1700 1.3~1.6 Non-uniformity of the barrier layer interface, generation of microbubbles 7.2 5.9 2.6 ±14 Reduced blocking ability Comparative Example 3 700~1600 1.3 or higher Adhesive layer continuity, pattern collapse 3.5 2.4 3.8 ±26 Non-uniform peeling Comparative Example 4 1500~2400 >1.3 Increased interfacial residual stress, long-term instability 3.6 2.5 3.1 ±21 Increased time dependence
[0237] For each film prepared according to Example 1 and Comparative Examples 1 to 4 above, oxygen transmission rate (OTR), water vapor transmission rate (WVTR), and 180° peel strength were measured. Oxygen transmission rate was measured at 23°C and 0% relative humidity, and water vapor transmission rate was measured at 38°C and 90% relative humidity. In addition, peel strength was measured at 180° at a speed of 300 mm / min, and 10 repeated measurements were performed for each specimen to calculate the average value and deviation.
[0238] As a result, in Example 1, the melt viscosity of each layer was formed in the range of approximately 900 to 1800 Pa·s under the same shear rate conditions, and the interlayer viscosity ratio was precisely controlled in the range of 0.8 to 1.3, thereby ensuring flow stability at the interface and showing almost no interfacial wave or thickness variation. Accordingly, the oxygen permeability was found to be very low at approximately 3.2 cc / m²·day and the water vapor permeability at approximately 2.1 g / m²·day, while the 180° peel force was stably maintained at approximately 2.4 N / 25mm and the peel variation also showed very uniform behavior at ±6%.
[0239] On the other hand, in Comparative Example 1, as the interlayer viscosity ratio of the substrate layer (110) increased to a level of 1.4 to 1.8, interfacial shear instability occurred due to the difference in flow velocity between adjacent layers, and an expansion of the interfacial wave and thickness deviation was observed. As a result, the oxygen permeability increased to about 4.8 cc / m²·day and the water vapor permeability increased to about 3.6 g / m²·day, and the peeling strength also showed a tendency to increase in average value, but the peeling deviation expanded to a level of ±18%, resulting in a problem of reduced uniformity.
[0240] In Comparative Example 2, the viscosity ratio between each blocking layer of the high-blocking layer (120) was formed to a level of 1.3 to 1.6, resulting in an interfacial flow imbalance. In particular, as thermal stability and flow stability were simultaneously reduced in the third blocking layer (123) containing PVDC, microbubbles and interfacial discontinuous structures were formed. As a result, the formation of a tortuous path was inhibited, causing the oxygen permeability to increase significantly to about 7.2 cc / m²·day and the water vapor permeability to increase significantly to about 5.9 g / m²·day, resulting in a significant decrease in blocking performance. In the case of peeling force, the average value was similar to that of the example, but the peeling deviation increased to ±14% due to interfacial non-uniformity.
[0241] In Comparative Example 3, the composition of each layer and the adhesive composition of the interfacial peeling force control layer (130) were formed outside the range of Example 1, and the interlayer viscosity ratio also increased to 1.3 or higher, resulting in an uneven distribution of shear stress within the interface. In particular, the adhesive layer applied in a semi-continuous pattern partially transitioned into a continuous film form due to insufficient viscosity stability, and thus the energy release rate distribution across the entire interface could not be maintained uniformly. Consequently, peeling initiation occurred intensively at specific locations and exhibited a rapid fracture pattern, resulting in an increase in the 180° peeling force to approximately 3.8 N / 25 mm and a significant expansion of the peeling deviation to ±26%.
[0242] Comparative Example 4 was formed under conditions where the melt viscosity increased due to a change in the composition of the protective layer (140), and as a result, the viscosity ratio with the fourth protective fusion layer (134) exceeded 1.3, resulting in a decrease in flow compatibility at the interface and an increase in residual stress. In particular, as the cooling rate increased due to the low cooling roll temperature, stress relaxation was not sufficiently achieved in the protective layer in a high-viscosity state and it became fixed at the interface. As a result, the initial blocking performance was maintained at a level similar to the example, but the peeling force increased to about 3.1 N / 25 mm, and the peeling deviation also expanded to ±21%, causing a problem where the peeling behavior fluctuated in a time-dependent manner during long-term storage.
[0243] As such, it can be confirmed that in Comparative Examples 1 to 4, when the control of viscosity or viscosity ratio in the substrate layer, high barrier layer, interface peel force control layer, and protective layer deviates from the range of Example 1, the interface flow stability is reduced and problems such as interface wave formation, microbubbles, non-uniform adhesion, or increased residual stress occur. In contrast, it was confirmed that Example 1 can maintain a uniform distribution of energy release rate at the interface and simultaneously secure high barrier properties and uniform peelability by precisely controlling the viscosity and viscosity ratio within a certain range across the entire layer.
Claims
Claim 1 A high-barrier film comprising a substrate layer, a high-barrier layer laminated on the substrate layer, an interface peel force control layer laminated on the high-barrier layer, and a protective layer laminated on the interface peel force control layer, wherein the substrate layer is formed in a multilayer structure comprising polyethylene terephthalate, polypropylene, and polyamide, and the interface peel force control layer comprises a first interface adhesion control layer, a second stress buffer layer, a third peel inducing layer, and a fourth protective fusion layer, and wherein the first interface adhesion control layer, the second stress buffer layer, and the third peel inducing layer are integrally formed by a multilayer co-extrusion process, characterized in that the interface peel control type multilayer film for cosmetic containers Claim 2 The interface peeling control type multilayer film for cosmetic containers according to claim 1, wherein the high barrier layer comprises an ethylene-vinyl alcohol copolymer, polyvinylidene chloride, and polyamide. Claim 3 The interface peeling control type multilayer film for cosmetic containers according to claim 1, characterized in that the protective layer comprises a fluorine-based resin, a silicone-based resin, and a urethane-based resin. Claim 4 delete Claim 5 The interface peeling control type multilayer film for cosmetic containers according to claim 1, wherein the high barrier layer or protective layer includes synthetic beads, and the synthetic beads are formed from at least one of acrylic, polystyrene, polymethyl methacrylate, urethane, and melamine resin. Claim 6 The interface peeling-controlling multilayer film for cosmetic containers according to claim 1, wherein the high barrier layer or protective layer comprises inorganic particles, and the inorganic particles comprise at least one of nano clay, graphene oxide, plate-like silica, and plate-like alumina. Claim 7 delete
Citation Information
Patent Citations
Reusable polyolefin-based food packing material and method for manufacturing same
KR101492789B1
Transparent, weather-resistant barrier foil, production thereof by means of lamination, extrusion lamination or extrusion coating
KR1020120014161A
